Language, identity and stress: A situated approach to acculturation. - Noels, Kimberly Ann. (University of Ottawa (Canada), 1996)
Bilingualism is an important, if contentious, educational and socio-political issue, with implications for both society and individuals. This study considers several social psychological implications of developing second language (L2) competence by examining the links between ethnolinguistic identity, L2 self-confidence and efficiency, and psychological well-being. Participants included 368 Anglophone and 432 Francophone students attending a bilingual university. The results of confirmatory and exploratory fact or analyses showed that ethnic identity is multidimensional, and the number and types of factors depends upon the identity (L1-group vs. L2-group) and the language group (Anglophone vs. Francophone) considered. The extent of identification with each group differed according to the situation and the vitality of the group. In a similar manner, L2 self-confidence and L2-group contact varied as a function of group vitality, suggesting that contact and L2 competence mediate the link between vitality and identity. Indeed, correlational analyses confirmed the relations between contact, L2 self-confidence and identity in some situations. L2 self-confidence also mediated the connection between group contact, on the one hand, and proficiency and psychological well-being, on the other. These findings point to two major implications. First, future research should adopt a multidimensional, situational approach to the study of ethnic identity. Second, although developing L2 self-confidence may be associated with identity loss for some groups, it is also generally indicative of better mental health. Thus, whether bilingualism is an "additive" or a "subtractive" experience depends upon the outcome of interest.
Keywords: Education, Bilingual and Multicultural.